(Q)gis in analize prostorskih podatkov - Kamnik, Rok (University of Maribor Press, 2023)
(Q)GIS and Spatial Data Analysis. The (Q)GIS and spatial data analysis textbook covers part of the content of the exercises in the subjects GIS and spatial analysis, Selected chapters from geodesy and GIS, Geodesy/GIS - selected chapters, Basics of environmental planning and Environmental protection in traffic. As an aid in the acquisition, preparation, processing, analysis, display and storage of geographic spatial data, it can also be used by students of other faculties and fields of study who encounter the free software QGIS and spatial data processing. The content of the textbook is divided into the following sections: Introduction, Geographics information system, Web data and their preparation, QGIS, Working with QGIS and Conclusion.